Is it safe to breastfeed infants who have received hepatitis B vaccine at birth if the mother has chronic hepatitis B?. Issue 9 (September 2016) - Pierre, Elyse; Kelly, Christina
Abstract : Evidence‐Based Answer : There does not appear to be an increased rate of mother‐to‐child transmission of hepatitis B virus (HBV) in breastfed, vaccinated infants of mothers with chronic hepatitis B (CHB) compared with the rate of transmission in vaccinated infants who are not breastfed, regardless of the mother's degree of hepatitis B infectivity (SOR: B, meta‐analyses of cohort trials).